HARVARD BUSINESS ESSENTIALS : Business Communication (Boston, Mass : Harvard Business School Press, 2003)
"This practical guide offers readers a clear and comprehensive overview on how to communicate effectively for every business situation, from sensitive feedback to employees to persuasive communications for customers. It offers advice for improving writing skills, oral presentations, and one-on-one dealings with others"--Book jacket.
t The First Draft -- t t
Includes index
Includes bibliographical references
Keywords: Business communication; Communication dans l'entreprise